REKONSTRUKSI KEWENANGAN PENYIDIKAN BADAN NARKOTIKA NASIONAL BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - M. Sahid (Arena Hukum, 2014)
AbstractAuthority to conduct criminal investigations of narcotic regulated under Law No. 35 of 2009 on Narcotics, namely article 81 of the law. Dibeikan investigative authority to the national drug agencies and the police of the republic of Indonesia. With the division of the investigative authority of overlap and multiple interpretations of article 81 of Law No 35 of 2009 on Narcotics. This paper aims to analyze the rules of authority narcotics investigation of criminal offenses. This paper is based on research using the normative approach to law (statute approach) and the conceptual approach (conceptual approach). The results showed that the regulation of narcotic crime investigation authority should be clarified and given limit, so in practice the rule of law is not a clash of authority between the National Narcotics Agency to police the Republic of Indonesia. As well as law enforcement agencies in carrying out their duties effectively and goes in accordance with the criminal justice system. Key words: authority investigation, crime, narcotics Â AbstrakKewenangan melakukan penyidikan tindak pidana narkotika diatur didalam Undang-undang Nomor 35 Tahun 2009 tentang Narkotika yaitu Pasal 81 Undang-undang tersebut. Kewenangan penyidikan diberikan kepada Badan Narkotika Nasional dan Kepolisian Republik Indonesia. Dengan adanya pembagian kewenangan penyidikan tersebut terjadi tumpang tindih dan multi tafsir terhadap Pasal 81 Undang-undang Nomor 35 Tahun 2009tentang Narkotika. Tulisan ini bertujuan untuk menganalisis aturan tentang kewenangan penyidikan terhadap tindak pidana narkotika. Tulisan ini dibuat berdasarkan penelitian normatif dengan menggunakan pendekatan perundang-undangan (Statute Approach) dan pendekatan konsep (Conceptual Approach). Hasil penelitian menunjukkan bahwa pengaturan mengenai kewenangan penyidikan tindak pidana narkotika harus diperjelas dan diberi batasan, sehingga dalam praktek penegakan hukum tidak terjadi benturan kewenangan antara Badan Narkotika Nasional dengan Kepolisian Republik Indonesia. Serta lembaga penegak hukum dalam menjalankan tugasnya berjalan dengan efektif dan sesuai dengan sistem peradilan pidana. Kata kunci:kewenangan penyidikan, tindak pidana, narkotika